Phylogeny of Vibrio vulnificus from the Analysis of the Core-Genome: Implications for Intra-Species Taxonomy - Roig, Francisco J.; González-Candelas, Fernando; Sanjuán, Eva; Fouz, Belén; Feil, Edward J.; Llorens, Carlos; Baker-Austin, Craig; Oliver, James D.; Danin-Poleg, Yael; Gibas, Cynthia J.; Kashi, Yechezkel; Gulig, Paul A.; et al. (Frontiers in Microbiology, 2018)
Vibrio vulnificus (Vv) is a multi-host pathogenic species currently subdivided into three biotypes (Bts). The three Bts are human-pathogens, but only Bt2 is also a fish-pathogen, an ability that is conferred by a transferable virulence-plasmid (pVvbt2). Here we present a phylogenomic analysis from the core genome of 80 Vv strains belonging to the three Bts recovered from a wide range of geographical and ecological sources. We have identified five well-supported phylogenetic groups or lineages (L). LI comprises a mixture of clinical and environmental Bt1 strains, most of them involved in human clinical cases related to raw seafood ingestion. LII is linked to the aquaculture industry and includes Bt3 strains exclusively, mostly related to wound infections or secondary septicemia after farmed-fish handling. LIII is formed by a mixture of Bt1 and Bt2 strains from various sources, including diseased fish, and is also related to the aquaculture industry. Lastly, LIV and LV include a few strains of Bt1 associated with specific geographical areas. The phylogenetic trees for ChrI and II are not congruent to one another, which suggests that inter- and/or intra-chromosomal rearrangements have been produced along Vv evolution. Further, the phylogenetic trees for each chromosome and the virulence plasmid were also not congruent, which also suggests that pVvbt2 has been acquired independently by different clones, probably in fish farms. From all these clones, the one with zoonotic capabilities (Bt2-Serovar E) has successfully spread worldwide. From these results, we propose a new updated classification of the species based on phylogenetic lineages rather than on Bts, as well as the inclusion of all Bt2 strains in a pathovar with the particular ability to cause fish vibriosis, for which we suggest the name “piscis”.